“China Shocks” And Their Employment Effects In Emerging Economies - Bambang Suprayogi; Tarek M Harchaoui (Politeknik Kutaraja, 2020)
The impact of “China shocks” on trading partners is a source of a massive supply shock that displaces foreign manufacturing producers, combined with an important source of demand shock that propelled forward a wide range of foreign sectors including those producing primary products, intermediates, and services. Yet, much of the emphasis of the literature has been placed on the supply shock and its impact, leaving a large span of “China shocks” unexplained. We undertake the important task to account for the dual track of “China shocks” and their impacts on a representative set of emerging economies (Brazil, India, Indonesia, Mexico and Turkey) for which the evidence remains scanty and not directly comparable. Using a global input-output accounting framework which highlights the job creation aspect of exports along with the job destruction aspect of imports, we provide evidence on the employment effect of bilateral trade with China over the 1995-2011 period. Our results suggest that considering the net effect of supply and demand related to China shocks leads to 3.7 million job losses for these economies, compared to 11.8 million if only the supply shock has been considered